The future of soft loans as an instrument of development finance: An assessment - Livia Fritz; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2014)
Within the framework of the Post-2015 Development Agenda, discussions on Financing for Development and the future of ODA have intensified recently. Amongst the many financial instruments that are potentially under review, are soft loans. Combining tied aid with concessional financing, soft loans are of a hybrid nature, involving both export promotion interests and development objectives. A recent ÖFSE research project took a closer look at the institutional evolution and the current status quo of soft loan financing in Europe. Upon that basis, scenarios for the future use of soft loans as an instrument of development finance are presented.
Keywords: 330; Entwicklungshilfe; Internationaler Kredit; Entwicklungsfinanzierung; EU-Staaten